Nitrogen fluorescence emission pumped by femtosecond optical vortex beams - Chen, You; Man, Xiaoman; Liu, Binxian; Lin, Zhiyang (Frontiers in Physics, 2023)
An experimental investigation on nitrogen fluorescence emissions pumped by a single 800 nm fs optical vortex (OV) beam with different topological charges (TC) is reported. The intensity of the two prototype emission lines from neutral nitrogen molecules (N2) and molecular nitrogen ions (N2+), i.e., 337 nm and 391 nm, respectively, shows different TC dependences: the former slightly decreases as the TC increases, while the latter sharply decreases as the TC changes from zero to a non-zero value. The dependences of the 337-nm and 391-nm emission intensity on pulse energy are also different: the former shows a linear variation for different TCs, while the latter has an abrupt change in the slope when changing the TC. Furthermore, the dependence of the 337-nm emission intensity on gas pressure exhibits a plateau which is universal for different TCs. In contrast, the dependence of the 391-nm emission intensity on gas pressure shows an apparent hump which is respective of the TC. These actual new results will facilitate further theoretical study on the formation dynamics of the nitrogen fluorescence emissions induced by the OV beam, and inspire that such beam can been taken as a unique pure optical tool to manipulate the transitions between different electronic-vibrational states.